Healing Methods of Mental Disorders with Malukat: The Perspective of Balinese Culture - Grantika, Putu Agus; IGA Indah Ardani; IGA Endah Ardjana (HM Publisher, 2020)
Balinese culture is known for its strong belief in spiritual influences on the occurrence of illnesses, especially mental disorders. Balinese people still believe that two factors cause mental disorders. The first factor is the real natural factor or Sekala where people will come to the doctor, and the second factor is the unreal natural factor or Niskala where people will consult the paranormal, traditional healer or Balian. In this study, a case was found, where a Balinese teenager experienced a mental disorder. Healing with the traditional Malukat method was used in this case. With this ceremony, it is hoped that all contamination, dirt, and disease will disappear and return to their homeostasis state.